Penerapan Pembelajaran Matematika Realistik Berbasis Multimedia terhadap Peningkatan Kemampuan Penalaran Adaptif Siswa MTs - Moch. Nurkholis; Uba Umbara (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2017)
using realistic mathematics education Basedon multimedia to increase the students of MTs adaptive reasoning skills. Thebackground of this study is to improve the students Adaptive reasoning skills byusing Realistic mathematics Education Based on multimedia. The result of theinitial test indicates that the average value of control class is 4,45 and the averagevalue of experimental class is 5,1. Meanwhile the result of the final test shows thatthe average value of control class is 9,6 and the average value of experimentalclass is 11,8. Based on the outcome of the initial and final data analysis, it can beconcluded that learning realistic mathematics education based on Multimedia isbetter than konventional learning. Howefer, the increase of adaptive reasoningskills in experimental classes in middle category. In addtion, the results ofquestionnaire responses students showed a positive response to the realisticmathematics education based on multimedia.